Adalimumab induced alopecia areata in a patient with arthritis. - Aydemir, A.T.; Oktem, A.; Avar Aydın, P.O.; Özcakar, Z.B.; Kundakcı, N. (European Journal of Pediatric Dermatology, 2024)
The use of biologic agents such as anti-TNF alpha inhibitors in chronic inflammatory diseases is increasing. Consequently, skin side effects such as infusion reactions, psoriasis and alopecia have been observed. Knowing how to recognize these side effects is necessary to reach the correct diagnosis and treatment.